Evaluasi Program Adiwiyata dalam Meningkatkan Kesadaran Lingkungan Siswa dengan Menggunakan Model CIPP di SMP Negeri 39 Jakarta - Siburian, Rumia; Sihotang, Hotmaulina (Kelola: Jurnal Manajemen Pendidikan, 2025)
This study aims to evaluate the implementation and effectiveness of the Adiwiyata program in fostering environmental awareness in schools. Using a descriptive qualitative approach with a program evaluation method based on Stufflebeam’s CIPP model (Context, Input, Process, Product), the research involved teachers participating in the program’s implementation selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and validated using source, technique, and time triangulation to ensure credibility. Data analysis was conducted thematically according to the CIPP components to assess the program’s context, input, process, and product. The results indicate that although schools have shown commitment and there have been positive changes in environmentally friendly behavior, the level of environmental awareness and internalization of environmental values among students still needs improvement. The Adiwiyata program has not yet fully succeeded in establishing a consistent culture of environmental care. Therefore, it is recommended to strengthen the role of teachers through training, integrate environmental material contextually into the curriculum, and improve routine habituation and monitoring systems to embed environmental care values more deeply and sustainably.